Model-based teaching and learning about inheritance in third-grade science. Issue 15 (13th October 2019) - Cisterna, Dante; Forbes, Cory T.; Roy, Ranu
ABSTRACT: Research suggests that it is challenging for elementary students to develop conceptual understanding of trait variation, inheritance of traits, and life cycles. In this study, we report on an effort to promote elementary students' learning of hereditary-related concepts through scientific modelling, which affords opportunities for elementary students to generate visual representations of structure and function associated with heredity. This study is part of a four-year design-based research project aimed at supporting students' learning about life science concepts using corn as a model organism. Study data were collected during the implementation of a project-developed, multi-week, model-based curriculum module in eight third-grade classrooms located in the Midwestern United States. Through mixed methods research, we analysed video recorded observations of curriculum implementation, student artefacts, and student interviews. Results illustrate epistemic dimensions of model-based explanations (MBEs) for heredity that students prioritised, as well as significant variation in students' MBEs in 2 of the 8 classrooms. While findings show neither students' content knowledge nor model-based instruction associated with their MBEs, qualitative differences in teachers' curriculum enactment, and more general approaches to science instruction, may help explain observed differences. Implications are discussed for curriculum and instruction in support of students' MBE for heredity-related concepts.